Development of Multiplex Assays for the Identification of Zoonotic Babesia Species - Calchi, Ana Cláudia [UNESP]; Moore, Charlotte O.; Bartone, Lillianne; Kingston, Emily; André, Marcos Rogério [UNESP]; Breitschwerdt, Edward B.; Maggi, Ricardo G. (MDPI, 2024)
More than one-hundred Babesia species that affect animals and humans have been described, eight of which have been associated with emerging and underdiagnosed zoonoses. Most diagnostic studies in humans have used serology or molecular assays based on the 18S rRNA gene. Because the 18S rRNA gene is highly conserved, obtaining an accurate diagnosis at the species level is difficult, particularly when the amplified DNA fragment is small. Also, due to its low copy number, sequencing of the product is often unsuccessful. In contrast, because the Babesia internal transcribed regions (ITS), between 18S rRNA and 5.8S rRNA, and between 5.8S rRNA and 28S rRNA, contain highly variable non-coding regions, the sequences in these regions provide a good option for developing molecular assays that facilitate differentiation at the species level. In this study, the complete ITS1 and ITS2 intergenic regions of different Piroplasmida species were sequenced to add to the existing GenBank database. Subsequently, ITS1 and ITS2 sequences were used to develop species-specific PCR assays and specific single-plex and multiplex conventional (c)PCR, quantitative real-time (q)PCR, and digital (d)PCR assays for four zoonotic Babesia species (Babesia divergens, Babesia odocoilei, Babesia duncani, and Babesia microti). The efficacy of the assay protocols was confirmed by testing DNA samples extracted from human blood or enrichment blood cultures. Primers were first designed based on the 18S rRNA-5.8S rRNA and 5.8S rRNA-28S rRNA regions to obtain the ITS1 and ITS2 sequences derived from different Piroplasmida species (B. odocoilei, Babesia vulpes, Babesia canis, Babesia vogeli, Babesia gibsoni, Babesia lengau, Babesia divergens-like, B. duncani, B. microti, Babesia capreoli, Babesia negevi, Babesia conradae, Theileria bicornis, and Cytauxzoon felis). Subsequently, using these sequences, single-plex or multiplex protocols were optimized targeting the ITS1 region of B. divergens, B. microti, and B. odocoilei. Each protocol proved to be sensitive and specific for the four targeted Babesia sp., detecting 10−2 (for B. microti and B. odocoilei) and 10−1 (for B. divergens and B. duncani) DNA copies per microliter. There was no cross-amplification among the Babesia species tested. Using 226 DNA extractions from blood or enrichment blood cultures obtained from 82 humans, B. divergens (seven individuals), B. odocoilei (seven individuals), and B. microti (two individuals) were detected and identified as a single infection, whereas co-infection with more than one Babesia sp. was documented by DNA sequencing in six (7.3%) additional individuals (representing a 26.8% overall prevalence). These newly developed protocols proved to be effective in detecting DNA of four Babesia species and facilitated documentation of co-infection with more than one Babesia sp. in the same individual.
Keywords: babesiosis; diagnosis; tick-borne diseases; zoonotic Babesia